Karyological Studies on Nine Astragalus L. Taxa in Turkey - Gedik, Osman; Kursat, Murat; Kiran, Yasar (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2019)
The somatic chromosome number and morphometric properties of nine Astragalus taxa native to Turkey were studied in detail. Somatic chromosome numbers have been determined as follows: A. campylorhynchus Fisch. & C.A. Mey., A. suberosus Banks & Sol., A. densifolius Lam. subsp. densifolius, A. cretaceus Boiss., A. leporinus Boiss. var. hirsutus (Post) Chamberlain, A. anthylloides Lam., A. odoratus Lam. 2n=16, A. lamarckii Boiss. 2n=32, A. camptoceras Bunge, diploid chromosome number 2n=2x=16 and 2n=4x=32 tetraploid were seen in the cells. Chromosomes of Astragalus taxa, whose karyotype analyses were made, generally had metacentric and sub-metacentric chromosomes. In A. densifolius Lam. subsp. densifolius taxon, one pair satellite chromosomes (sat-chromosome) were observed. Among the species A. leporinus var. hirsutus and A. lamarckii were identified for the first time.
Keywords: Astragalus; Chromosome number; karyotypes; mitosis; Turkey